KONSEP PERANAN LAKI-LAKI DAN PEREMPUAN - Erniati, Erniati (Musawa: Journal for Gender Studies, 2019)
The concept of the roles of men and women basically has the right to obtain gender justice, especially to women. Gender justice is meant is the degree and equal position between men and women in society to carry out activities in various fields such as the field of work in particular. So the concept of gender is that women can gain freedom to move outside the home such as studying, working as an office employee without any pressure so that women will have the same degree as men and there is no oppression against women anymore.